Comparison of autologous bone marrow and adipose tissue derived mesenchymal stem cells, and platelet rich plasma, for treating surgically induced lesions of the equine superficial digital flexor tendon. (June 2017) - Romero, A.; Barrachina, L.; Ranera, B.; Remacha, A.R.; Moreno, B.; de Blas, I.; Sanz, A.; Vázquez, F.J.; Vitoria, A.; Junquera, C.; Zaragoza, P.; Rodellar, C.
Highlights: The effects of mesenchymal stem cells (MSCs) or platelet rich plasma (PRP) on tendon healing in horses were studied. Ultrasonographic improvement was earliest following treatment with bone marrow (BM)-derived MSCs (BM-MSCs). Histological evidence of healing was best with BM-MSCs and PRP, followed by adipose tissue (AT)-derived MSCs (AT-MSCs). Expression of genes associated with improved tendon healing was enhanced after all treatments, especially BM-MSCs. The most beneficial effects on tendon healing resulted from treatment with BM-MSCs, followed by PRP and AT-MSCs. Abstract: Several therapies have been investigated for equine tendinopathies, but satisfactory long term results have not been achieved consistently and a better understanding of the healing mechanism elicited by regenerative therapies is needed. The aim of this study was to assess the separate effects of autologous bone marrow (BM) and adipose tissue (AT) derived mesenchymal stem cells (MSCs), and platelet rich plasma (PRP), for treating lesions induced in the superficial digital flexor tendon (SDFT) of horses. Lesions were created surgically in both SDFTs of the forelimbs of 12 horses and were treated with BM-MSCs (six tendons), AT-MSCs (six tendons) or PRP (six tendons). The remaining six tendons received lactated Ringer's solution as control. Serial ultrasound assessment was performed prior to treatment and at 2, 6, 10, 20 and 45 weeks post-treatment. At 45 weeks, histopathology and gene expression analyses were performed. At week 6, the ultrasound echogenicity score in tendons treated with BM-MSCs suggested earlier improvement, whilst all treatment groups reached the same level at week 10, which was superior to the control group. Collagen orientation scores on histological examination suggested a better outcome in treated tendons. Gene expression was indicative of better tissue regeneration after all treatments, especially for BM-MSCs, as suggested by upregulation of collagen type I, decorin, tenascin and matrix metalloproteinase III mRNA. Considering all findings, a clear beneficial effect was elicited by all treatments compared with the control group. Although differences between treatments were relatively small, BM-MSCs resulted in a better outcome than PRP and AT-MSCs.